PENANAMAN NILAI-NILAI PENDIDIKAN ISLAM PADA PAUD REZEKI DESA KARTIASA KECAMATAN SAMBAS - Sri Nilawati; Hifza Hifza; Ubabuddin (CV. ADIBA AISHA AMIRA, 2023)
This study discusses the instilling of Islamic Religious Education Values in PAUD Rezeki Kartiasa Village, Sambas District. This thesis is motivated by the Internalization of Instilling Islamic Educational Values in Early Childhood At PAUD Rezeki Kartiasa Village as the 2nd (second) education place after education in the family environment. This research approach uses a qualitative approach with a Field Research pattern of research (field research). This study intends to examine the values of worship, creed, and morals and to reveal methods and evaluations in inculcating Islamic religious education in Early Childhood Education institutions. The results showed that the methods of inculcating Islamic religious education values in PAUD Rezeki Kartiasa Village were: a) Storytelling method, to instill moral values and exemplary; b) The singing method, to instill the values of spirit, life and awareness, because through the singing method children feel happy and happy; c) The method of playing, to instill moral values related to the attitude of being willing to give in, cooperation, helping, queuing culture and respect for friends; d) The exemplary method, to instill moral values so that they can behave and speak well and appropriately; and e) Question and answer method, to instill the value of courage and initiative.